2014
DOI: 10.1093/jxb/eru123
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene negatively regulates aluminium-induced malate efflux from wheat roots and tobacco cells transformed with TaALMT1

Abstract: SummaryExudation of malate is an important mechanism underlying tolerance of wheat to aluminium toxicity. Here we show that ethylene is involved in regulation of ALMT1-dependent malate efflux from wheat roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 66 publications
3
35
0
Order By: Relevance
“…Similar to auxin, which has long been known to play a critical role in Al-induced root growth inhibition (Kollmeier et al, 2000;Sun et al, 2010), ethylene has also been reported to be important in Al-induced root growth inhibition in common bean (Massot et al, 2002;Eticha et al, 2010), Lotus japonicus (Sun et al, 2007), Arabidopsis , and wheat (Triticum aestivum; Tian et al, 2014b). Also, the potential participation of the auxinethylene interaction in the regulation of Al-induced root growth Al stress induces TAA1 local upregulation (shown by TAA1:GFP) in the TZ through an ethylene-dependent pathway, thus inducing local auxin accumulation and an auxin signaling maximum in the TZ (shown by DR5rev:GFP) and inhibition of root growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to auxin, which has long been known to play a critical role in Al-induced root growth inhibition (Kollmeier et al, 2000;Sun et al, 2010), ethylene has also been reported to be important in Al-induced root growth inhibition in common bean (Massot et al, 2002;Eticha et al, 2010), Lotus japonicus (Sun et al, 2007), Arabidopsis , and wheat (Triticum aestivum; Tian et al, 2014b). Also, the potential participation of the auxinethylene interaction in the regulation of Al-induced root growth Al stress induces TAA1 local upregulation (shown by TAA1:GFP) in the TZ through an ethylene-dependent pathway, thus inducing local auxin accumulation and an auxin signaling maximum in the TZ (shown by DR5rev:GFP) and inhibition of root growth.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the potential participation of the auxinethylene interaction in the regulation of Al-induced root growth Al stress induces TAA1 local upregulation (shown by TAA1:GFP) in the TZ through an ethylene-dependent pathway, thus inducing local auxin accumulation and an auxin signaling maximum in the TZ (shown by DR5rev:GFP) and inhibition of root growth. inhibition has been suggested Tian et al, 2014b), while the exact interaction mechanism during Al-induced inhibition of root growth is still undetermined. Here, our results indicate that, in response to Al stress, ethylene induces local TAA1 upregulation and thus the auxin signaling maximum in the root-apex TZ, inducing root growth inhibition (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…6.1 ). Besides, Al toxicity-mediated changes in plant ethylene production have been observed to cause changes in malate anion concentrations (Tian et al 2014 ; Fig. 6.1 ).…”
Section: Phytohormonal Responses To Aluminum Toxicitymentioning
confidence: 98%
“…Furthermore, application of ethylene biosynthetic inhibitor aminoethoxyvinylglycine (AVG) or perception inhibitor Co 2+ (Abeles et al 1992 ) resulted in a decrease in ethylene production or activity, respectively, as well as eliminating the root elongation inhibition caused by Al toxicity after 12 h (Sun et al 2007 ). Recently, Tian et al ( 2014 ) demonstrated that the increase in ethylene production in root apex and the inhibition of root elongation in wheat plants exposed to Al toxicity were both ameliorated by a pretreatment of Al-stressed plants with 2-aminoisobutyric acid (AIB), an inhibitor of both ACC synthase and oxidase activities (Abeles et al 1992 , Fig. 6.1 ).…”
Section: Phytohormonal Responses To Aluminum Toxicitymentioning
confidence: 99%
See 1 more Smart Citation